1999
DOI: 10.1034/j.1399-3054.1999.100305.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of pectic polysaccharides in cell walls, extracellular polysaccharides, and glycan‐hydrolytic enzymes of growth‐restricted carrot cells under calcium deficiency

Abstract: Suspension‐cultured carrot (Daucus carota L. cv. Kintoki) cells were grown in calcium (Ca2+)‐deficient and normal liquid media. Cell growth was limited by the Ca2+ deficiency. Similar amounts of pectic fractions were extracted from the walls of control and Ca2+‐deprived cells, but the fractions from the walls of Ca2+‐deprived cells showed a substantial decrease in galacturonic acid content. However, after 15 days of culture, Ca2+‐deprived cells released galacturonic acid‐rich extracellular polysaccharides at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Calcium is directly involved in the processes of cell division in the meristematic zones of plants, affecting their viability and bud formation and, consequently, the plant's multiplication rate. Calcium also participates in the synthesis of pectin molecules involved in cell wall formation (Konno et al, 1999), and the lack of this element may alter the structure and metabolism of the pectin molecules, reducing the mitotic index in these plants. Additionally, reduction of the calcium content in tissues cultivated in vitro is directly related to physiological disorders such as necrosis of the apex and vitrification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium is directly involved in the processes of cell division in the meristematic zones of plants, affecting their viability and bud formation and, consequently, the plant's multiplication rate. Calcium also participates in the synthesis of pectin molecules involved in cell wall formation (Konno et al, 1999), and the lack of this element may alter the structure and metabolism of the pectin molecules, reducing the mitotic index in these plants. Additionally, reduction of the calcium content in tissues cultivated in vitro is directly related to physiological disorders such as necrosis of the apex and vitrification.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen is essential for normal growth and development in plants, and plays an important role in regulating of many physiological functions (Konno et al, 1999;Ramage & Williams, 2002). Leljak-Levanic et al (2004) demonstrated that NH 4 + and NO 3 -concentrations in the culture medium affect numerous morphogenetic responses, including the development of callus tissue and somatic embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium plays an important role in regulating the structure and properties of the network of pectic molecules in cell walls. Apoplastic Ca regulates the deposition of non-cellulosic polysaccharides in cell walls of spruce (Eklund and Eliasson, 1990) and flax hypocotyl (His et al, 1997) seedlings and carrot cell cultures (Konno et al, 1999). However, since Ca was found in almost similar amounts in the control and Cu-treated cell walls, the difference in the pectin extraction from the two cell walls could not be due to a difference in the Ca concentration in the cell walls.…”
Section: Analysis Of Pectic and Hemicellulosic Polysaccharides In Celmentioning
confidence: 95%
“…Cell wall-associated Ca 21 maintains cell wall integrity by generating cross-links with nonesterified pectins in the primary cell wall and middle lamella (Jarvis, 1984;Poovaiah et al, 1988 -pectin bridges prevents the access of cell wall hydrolytic enzymes, thus inhibiting cell wall expansion (Jauneau et al, 1994;Konno et al, 1999). Further work is required to demonstrate that cell wall-associated Ca 21 levels are indeed enhanced in CAX-expressing plants compared to wild type.…”
Section: Discussionmentioning
confidence: 99%